Disgestibilidade in vitro de milho moído sob três níveis de enzima amilolítica exógena - Assis, Paula Lobo Ferreira (2012)
In cattle, the number is constant research involving feed additives, in order to achieve high productivity and improvements in diet formulation. Among the alternative additives there are the enzymes which are proteins catalysts of chemical reactions involved in the metabolic process the entire animal organism. The efficiency of enzymes in diets based on alternative foods has encouraged its use, representing a major breakthrough in nutrition. Enzyme complex in diets based on corn has as main objective the maximization of nutrients included in the diet and thereby improve outcomes husbandry. This study aimed to produce an amylolytic enzyme complex, using the fungus Aspergillus awamorii and evaluate the in vitro digestibility of corn subjected to three levels of exogenous enzyme amylase. The treatments were: control (without enzyme), the first level (with 5 ml of enzyme), level 2 (with 10 ml of enzyme) and level 3 (20 ml enzyme). The experiment was conducted in the Laboratório de Enzimologia e Laboratório de Fisiologia da Digestão do Instituto de Ciências Biológicas/ICB II, da Universidade Federal de Goiás. The addition of amylolytic enzymes had a positive influence on increasing the degradation of corn at level 3 until the time of 24h compared to control treatment, this fact may be attributable to enzymatic activity on the substrate from the time that the enzyme was applied. At the time of 48 hours was not significantly different between treatments, indicating that there was compensation in the digestibility of dry matter between treatments after 24 hours for the control treatment and after 18 hours for levels 1 and 2, this fact may be coupled with the fact that there proteolytic activity in the rumen fluid present in the fermenter jars, which in turn can destroy the enzymes inactivating them. The time of colonization of maize was reduced by adding enzyme, which was attributed to the enzymatic action of increasing surface contact and providing oligosaccharides smaller chains for bacteria, providing better conditions for bacterial growth. In the present study doses with higher digestibility were 17.8 and 16.4 ml for times 0 and 24 hours incubation respectively, corresponding to 769.2 and 708.7 enzyme units / kg of dry corn. The addition of exogenous amylolytic enzymes improved the "in vitro" dry matter of ground corn with the level of enzyme addition to passage rates above 4%, between 708.7 and 769.2 units enzyme / kg Maize dry matter